Gambaran Karakteristik Pasien Penyakit Ginjal Kronik Yaang Menjalani Hemodialisa Di RSUP DR M.Djamil Padang - Adep Junika Adep (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Hemodialysis is a therapy carried out to help the kidneys remove the final results of the body's metabolism because the kidneys cannot carry out their functions due to damage to the nephrons, the functional organs of the kidneys. This study aims to describe the characteristics of chronic kidney disease patients undergoing hemodialysis so as to obtain information about the patient's condition and determine appropriate treatment management for the survival of hemodialysis patients. This research uses a quantitative descriptive design, data collection uses questionnaires and direct observation. The number of respondents was 68 respondents. The data obtained was processed statistically using a frequency distribution. The results of this research show that the majority of respondents were male, 37 respondents (54.4%), a small number were female, 31 respondents (45.6%). In terms of age, there were 65 respondents (95.6%) in the adult category and 3 respondents (4.4%) in the elderly category. In terms of education, 48 respondents (70.6%) had low education and 20 respondents (29.4%) had high education. Furthermore, from job characteristics, 44 respondents (64.7%) did not work and 24 respondents (35.3%) worked. Then regarding marital status, 66 respondents (97.1%) were married and 2 respondents (2.9%) were not married.